Colombia : Arrangement Under the Flexible Credit Line and Cancellation of Current Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Colombia's Arrangement Under the Flexible Credit Line (FCL) and Cancellation of Current Arrangement. Growth is expected to accelerate in 2018 and further over the medium term underpinned by a rebound in investment and nontraditional exports. Although the ongoing recovery in global growth has reduced some near-term external risks, global financial markets are vulnerable to a sudden, sharp tightening of financial conditions as a result of an unexpected increase in inflation and/or an escalation of trade or geopolitical tensions. Colombia's exposure to some of these tail risks has increased in line with larger foreign participation in the local government debt market. The IMF staff's assessment is that Colombia continues to meet the qualification criteria for access to FCL resources.